Evidence of pseudoprogression in patients treated with PD1/PDL1 antibodies across tumor types. (19th February 2020) - Martin‐Romano, Patricia; Castanon, Eduardo; Ammari, Samy; Champiat, Stéphane; Hollebecque, Antoine; Postel‐Vinay, Sophie; Baldini, Capucine; Varga, Andrea; Michot, Jean Marie; Vuagnat, Perrine; Marabelle, Aurélien; Soria, Jean‐Charles; et al.
Abstract: Background: PD(L)1 antibodies (anti‐PD(L)‐1) have been a major breakthrough in several types of cancer. Novel patterns of response and progression have been described with anti‐PD(L)‐1. We aimed at characterizing pseudoprogression (PSPD) among patients with various solid tumor types treated by anti‐PD(L)‐1. Methods: All consecutive patients (pts) enrolled in phase 1 trials with advanced solid tumors and lymphomas treated in phase I clinical trials evaluating monotherapy by anti‐PD(L)‐1 at Gustave Roussy were analyzed. We aimed to assess prevalence and outcome of PSPD across tumor types. We also intended to describe potential clinical and pathological factors associated with PSPD. Results: A total of 169 patients treated with anti‐PD(L)‐1 were included in the study. Most frequent tumor types included melanoma (n = 57) and non‐small cell lung cancer (n = 19). At first tumor evaluation 77 patients (46%) presented with immune unconfirmed progressive disease. Six patients (8%) experienced PSPD: 2 patients with partial response; 4 patients with stable disease. Increase in target lesions in the first CT‐scan was more frequently associated to PSPD (67% vs 33%; P = .04). Patients with a PSPD had a superior survival when compared to patients progressing (median OS: 10.7 months vs 8.7 months; P = .07). Conclusions: A small subset of PSPD patients may experience response after an initial progression. Assessment of the current strategy for immune‐related response evaluations may require further attention. Abstract : PD(L)1 antibodies (anti‐PD(L)‐1) have been a major breakthrough in several types of cancer. Novel patterns of response and progression have been described with these therapies. We aimed at characterizing pseudoprogression (PSPD) among patients with various solid tumor types treated by anti‐PD(L)‐1